Credit Risk Determinants: Specific and Macroeconomic Factors of Islamic Banks - Rizqa, Agitsna Alya; Haryono, Slamet (Institut Agama Islam (IAI) SEBI, 2023)
The development of Islamic banking credit risk shows a downward trend. However, the existence of Indonesian Islamic banking in the world is not yet among the best ranked, even though it has the largest Muslim population. This study examines the factors that influence credit risk in Islamic banks in Indonesia by using the bank's specific characteristics and macroeconomic factors. This study uses a multiple linear regression method with monthly data on Islamic banking in Indonesia for the period 2020-2022. The dependent variable for credit risk uses Non-performing financing (NPF). Independent variables from bank-specific factors are used Capital Adequacy Ratio (CAR), Financing to Deposit Ratio (FDR), and Operating Expenses to Operating Income (BOPO). While the independent variables from macroeconomic factors use inflation and interest rates. The results showed that the CAR, FDR, and inflation variables affected the credit risk of Islamic banks. FDR has a positive effect, while CAR and inflation have a negative effect. BOPO and interest rates do not affect credit risk.